RESPONSE OF PIGEONPEA TO ZINC SULPHATE AND POTASSIUM UNDER RAINFED CONDITIONS IN WESTERN MANDALS OF CHITTOOR DISTRICT - Sahaja Deva , (The Journal of Research ANGRAU, 2024)
On-Farm Trials (OFTs) on yield enhancement in pigeonpea through basal application of Potassium and Zinc Sulphate were conducted at Krishi Vigyan Kendra, Kalikiri under rainfed conditions in selected areas of Chittoor district between 2017-18 and 2019-20 in field of five farmers in 2.0 ha during each year. Soil type was sandy loams. Treatments comprised Basal application of Zinc Sulphate (25 kg ha-1) + MOP (60 kg ha-1) + Nitrogen (20 kg ha-1), Phosphorus (50 kg ha-1) as Technology Option 1 and Basal application of FYM @ 20 q ac-1 as farmers practice. In TO1 Nitrogen @ 20 kg ha-1, Phosphorus @ 50 kg ha-1, Potash @ 60 kg ha-1 and Zinc Sulphate @ 25 kg ha-1 were applied to pigeonpea. In TO2 (Farmers practice) FYM @ 20 q ac-1 was applied.Yield attributes viz., number of pods per plant (223), 100 seed weight (11.1 g), yield (4.2 q ha-1) and B: C ratio (1.1) were significantly higher in case of treatment plot compared to check plot with number of pods per plant (194.3), 100 seed weight (9.2 g), yield (3.3 q ha-1) and B: C ratio (1.0)